2017
DOI: 10.1016/j.vaccine.2017.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Cost of a measles outbreak in a remote island economy: 2014 Federated States of Micronesia measles outbreak

Abstract: After 20 years with no reported measles cases, on May 15, 2014 the Centers for Disease Control and Prevention (CDC) was notified of two cases testing positive for measles-specific immunoglobulin M (IgM) antibodies in the Federated States of Micronesia (FSM). Under the Compact of Free Association, FSM receives immunization funding and technical support from the United States (US) domestic vaccination program managed by the Centers for Disease Control and Prevention (CDC). In a collaborative effort, public healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…From the 17 studies included in this review, four articles were from China (Jin et al, 2011 ; Ma et al, 2016 ; Ma et al, 2017 ; Zhang et al, 2015 ), three from Senegal (Cisse et al, 1999 ; Garenne & Aaby, 1990 ; Whittle et al, 1999 ), two from the Federated States of Micronesia (Hales et al, 2016 ; Pike et al, 2017 ), and one each from India (Rathi et al, 2017 ), Bolivia (Quiroga et al, 2003 ), Brazil (Lemos & Franco, 2017 ), Venezuela (Sarmiento et al, 2011 ), Republic of Marshall Islands (Marin et al, 2006 ), Romania (Njau et al, 2019 ), Tanzania(Goodson et al, 2010 ), and Ethiopia (Wallace et al, 2014 ). Eleven of the studies involved both male and female participants and the remaining six had no data on sex distribution of subjects (Garenne & Aaby, 1990 ; Marin et al, 2006 ; Pike et al, 2017 ; Quiroga et al, 2003 ; Sarmiento et al, 2011 ; Wallace et al, 2014 ). Most (88.2%) of the studies included both children and adults, but two studies included children (Whittle et al, 1999 ) and young adults (Jin et al, 2011 ) only.…”
Section: Resultsmentioning
confidence: 99%
“…From the 17 studies included in this review, four articles were from China (Jin et al, 2011 ; Ma et al, 2016 ; Ma et al, 2017 ; Zhang et al, 2015 ), three from Senegal (Cisse et al, 1999 ; Garenne & Aaby, 1990 ; Whittle et al, 1999 ), two from the Federated States of Micronesia (Hales et al, 2016 ; Pike et al, 2017 ), and one each from India (Rathi et al, 2017 ), Bolivia (Quiroga et al, 2003 ), Brazil (Lemos & Franco, 2017 ), Venezuela (Sarmiento et al, 2011 ), Republic of Marshall Islands (Marin et al, 2006 ), Romania (Njau et al, 2019 ), Tanzania(Goodson et al, 2010 ), and Ethiopia (Wallace et al, 2014 ). Eleven of the studies involved both male and female participants and the remaining six had no data on sex distribution of subjects (Garenne & Aaby, 1990 ; Marin et al, 2006 ; Pike et al, 2017 ; Quiroga et al, 2003 ; Sarmiento et al, 2011 ; Wallace et al, 2014 ). Most (88.2%) of the studies included both children and adults, but two studies included children (Whittle et al, 1999 ) and young adults (Jin et al, 2011 ) only.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we conducted a brief scoping review of the literature from January 2017 to May 2020 and found several articles that may have been eligible for inclusion post-2016. Particularly, we found two studies assessing the cost of measles in the Federated States of Micronesia [49] and the cost of measles and rubella in Romania [50] -a first for measles and rubella in LMIC. Other studies examined further the cost of GE [51][52][53][54][55][56][57][58][59], pneumonia [51,52,[59][60][61][62][63], and influenza [64,65].…”
Section: Limitations Of This Systematic Reviewmentioning
confidence: 99%
“…However, with declining stockpiles (yellow fever), the discovery of gaps in immunity in young adults (rubella) [8] and a sharp recrudescence of cases (measles), strategies to sustain and improve the coverage of these existing vaccines are at the forefront, potentially delaying the introduction of vaccines against other diseases. To our knowledge, there is no other empirical cost-of-illness study for measles in lowincome settings: only a few were done in lower-and uppermiddle-income countries [9][10][11].…”
Section: Introductionmentioning
confidence: 99%